Empowering Astronomical Exploration: Advancement of New Moon Observation Devices in Sarawak, Malaysia - Bely, Ahmad Hariz; Nasir, Ahmad Lutfi Afifi Mohd; Umar, Roslan; Chik, Wan Mohd Yusof Wan; Husaini, Razalie; Othman, Mohamad Shobri; Rakhmadi, Arwin Juli (Iraqi Journal of Science, 2024)
Understanding the motion of celestial objects is essential for space exploration. Observing the new crescent Moon requires advanced technological devices due to the moon’s position in the atmosphere and the refraction of sunlight on the horizon. Nowadays, theodolite and telescope applications are commonly used for new crescent moon sightings because they offer superior visibility compared to the naked eye. In Sarawak, the Falak Section holds the authority to observe the new crescent Moon to determine the beginning of the Hijree month. Thus, this study aims to examine the development of devices to observe the new moon crescent in the Sarawak Mufti Department. Qualitative methods are employed, involving the perspectives of astronomers and data on new crescent Moon observations using the observation devices in the Falak Section. From 1997 onwards, the Sarawak Mufti Department had three theodolites and seven telescopes specifically for new crescent moon observations. Additionally, there are 22 recorded data of new crescent Moon sightings using these devices. These findings indicate a direct correlation between the observation devices and the potential visibility of the new crescent Moon in Sarawak. This study will benefit the Sarawak Mufti Department in evaluating suitable devices for new crescent Moon observations, whether acquiring new devices or selecting devices for new crescent moon observations.